Violation of the right to privacy through artificial intelligence entities under the uae’s anti-cybercrime act - Al-Rai, Ashraf; Maala, Nermin; Almatri, Ghenaa; Khater, Maya (Research Journal in Advanced Humanities, 2026)
This study analyzes the legal framework for protecting the right to privacy, specifically in light of the widespread use of artificial intelligence (AI) technologies, within UAE legislation. The research centers on the extent to which substantive and procedural criminal protection is efficient and effective in addressing violations arising from the use of AI entities, especially given these systems’ significant ability to collect and analyze vast amounts of personal data, thereby influencing the behavior of individuals in society. The study adopts an analytical and descriptive approach, supported by a comparative perspective. The findings indicate that the right to privacy is fundamental one that ensures individuals’ control over their personal data and information. It was also found that AI technologies have created new forms of crimes, notably with the increasing spread of publishing personal images without consent and defamation through deep-fake technologies, which reflects the growing international concern that surrounds this issue. The study highlights the importance of enhancing societal awareness of digital privacy and the necessity of its protection, as well as recommending the establishment of specialized courts to handle cybercrimes. It also emphasizes the need to strengthen international cooperation to define the legal responsibilities of AI entities.